Socio-hydrology of “artificial glaciers” in Ladakh, India: assessing adaptive strategies in a changing cryosphere - Nüsser, Marcus; Dame, Juliane; Kraus, Benjamin; Baghel, Ravi; Schmidt, Susanne (Regional environmental change, 2018)
The consequences of even small glacier decrease and changes of seasonal snow cover are critical for the functioning of meltwater-dependent mountain agriculture. In order to deal with recurrent water scarcity, different types of ice reservoirs, commonly called “artificial glaciers,” have been introduced in Ladakh and promoted as appropriate adaptive strategies to cope with changes in the cryosphere. The resulting seasonal ice reservoirs increase meltwater availability during the critical period of water scarcity in spring. We examine the efficacy of 14 ice reservoirs through a long-term analysis of their functioning within the environmental and socioeconomic context of Ladakh. Using multi-temporal satellite data (1969-2017), close range photogrammetry, and repeat field measurements (2014 and 2015), we provide an inventory and typology of these ice reservoirs and estimate storage volume of one selected structure, which ranges from 1010 to 3220 m3 of water. We extrapolate this volume to all ice reservoirs and estimate potential irrigation cycles of cropped areas, which vary between less than 0.1 in unfavorable cases and almost 3 in optimal cases and years. Based on interviews and field surveys (2007-2017), we discuss the benefits perceived by local smallholders, such as the reduction of seasonal water scarcity and resulting crop failure risks together with the possibility of growing cash crops. We argue that “artificial glaciers” are remarkably suited to the physical environment. However, their usefulness as a climate change adaptation strategy is questionable because climatic variability, natural hazards, and an incomplete integration into the local socioeconomic setting significantly reduce their efficacy.